2014
DOI: 10.3389/fcimb.2014.00017
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydia exploit the mammalian tryptophan-depletion defense strategy as a counter-defensive cue to trigger a survival state of persistence

Abstract: We previously proposed that in Chlamydiaceae rapid vegetative growth and a quiescent state of survival (persistence) depend upon alternative protein translational profiles dictated by host tryptophan (Trp) availability. These alternative profiles correspond, respectively, with a set of chlamydial proteins having higher-than-predicted contents of Trp (“Up-Trp” selection), or with another set exhibiting lower-than-predicted contents of Trp (“Down-Trp” selection). A comparative evaluation of Chlamydiaceae proteom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 53 publications
(87 reference statements)
2
45
0
1
Order By: Relevance
“…polyamine biosynthesis, quorum sensing, DNA methylation, etc.). Recently, however, Bonner et al (63) have suggested that the synthesis of menaquinone, and thus enzymatic function of CT263, could be essential for Chlamydiaceae to maintain in a "persistent" state inside the host cell. Persistence is a reversible state of quiescence that Chlamydiaceae utilize as an immune evasion strategy (64).…”
Section: Discussionmentioning
confidence: 99%
“…polyamine biosynthesis, quorum sensing, DNA methylation, etc.). Recently, however, Bonner et al (63) have suggested that the synthesis of menaquinone, and thus enzymatic function of CT263, could be essential for Chlamydiaceae to maintain in a "persistent" state inside the host cell. Persistence is a reversible state of quiescence that Chlamydiaceae utilize as an immune evasion strategy (64).…”
Section: Discussionmentioning
confidence: 99%
“…This lead the authors to surmise C. trachomatis ocular strains might have a particular capacity for dissemination from the genital tract, and the small percentage of C. trachomatis cases progressing to CiA might reflect the small percentage of cases of in which ocular strains are found in genital infection [93]. C. trachomatis ocular strains and C. pneumoniae human strains, the chlamydiae commonly demonstrated to be involved in CiA, are unable to synthesize tryptophan and thus have increased sensitivity to the host IFN gamma response and subsequent tryptophan deprivation, a characteristic that might facilitate persistence as a means of initiating and maintaining chronic infection [94,95].…”
Section: Chlamydia-induced Arthritismentioning
confidence: 99%
“…infections. Tryptophan is, indeed, an important regulator of the chlamydial development cycle (Bonner et al, 2014). In case of tryptophan depletion, the expression pattern changes and forces the bacteria into a persistent form (Baud et al, 2008;Brunham & Rey-Ladino, 2005;Ibana et al, 2011).…”
Section: Metabolismmentioning
confidence: 99%